Disentangling the climatic and biotic factors driving changes in the dynamics of Quercus suber populations across the species' latitudinal range. Issue 4 (11th December 2018) - Matías, Luis; Abdelaziz, Mohamed; Godoy, Oscar; Gómez‐Aparicio, Lorena
Abstract: Aim: Impacts of different global change drivers are altering the performance of plant species worldwide. However, these pressures usually differ across the species' distribution range. To properly assess the combined effect of global change at species level, we need to evaluate its consequences across their complete distribution. We focused on recent decline in Cork oak ( Quercus suber L.) populations given its high ecological and economic relevance. Location: We selected 10 different sites (and two populations per site) separated about one degree in latitude across the core distribution of Q. suber, following a transcontinental aridity gradient. Methods: To evaluate the current trends in population dynamics across the species' distribution and the factors implied on population decline, we evaluated the effect of latitude, aridity, pathogens ( Phytophthora cinnamomi ), stand density and tree size on seed and crop size, demographic structure, dominance of recruitment bank, defoliation and mortality. Results: We found an increase in seed weight as latitude decreased, with a homogeneous low crop size across the complete distribution. Demographic structure was determined by latitude, precipitation and pathogen abundance. We detected a trend towards reduced sapling densities towards the southern edge of the distribution, with a demographic structure dominated by old trees. The low sapling density at the southern edge translates into a loss of dominance with respect to other woody species, suggesting an alteration of community structure in the mid‐term future. Tree density, precipitation and pathogen abundance determined tree mortality across the species distribution, with a higher abundance of pathogens in central‐latitude populations. Main conclusions: Our results allow the early detection of declining trends and the evaluation of the main risks for species' conservation, suggesting potential for range displacement of the species driven by the recruitment failure at the southern edge of the distribution and a likely range expansion at northern populations.